Overcoming challenges for the biorefineries of the future - Moirangthem, Kamaljit (2017)
Non-food lignocellulosic biomass is the most abundantly available raw material. Utilising it for biorefinery purposes not only circumnavigates the food vs fuel debate, but is also important for a complete move to a fossil fuel free society. Some of the major challenges in using lignocellulosic feedstock includes its recalcitrance, potential shortage for year-round mono feedstock supply and economic viability with current technology.